Innovations in Medicinal Chemistry for Cancer Treatment - Nathsharma, Santosh Kumar (AG Volumes, 2025)
Millions of people die each year from cancer, an aberrant condition of cells that produces aggressive tumours and unchecked cell multiplication. The development of several novel treatment regimens and their subsequent trials are a result of our growing understanding of the illness and its molecular mechanism of progression. Many malignancies are very difficult to diagnose and identify early. High death rates are always the result of late-stage cancer discovery. The development of new, more sensitive, and more efficient diagnostic and therapeutic techniques for cancer therapy is essential. Review the many studies on advances in medicinal chemistry for the treatment of cancer in this article. The study found that by improving medication biodistribution, allowing precision medicine, and reducing adverse effects, "nanomedicine, targeted therapy, and nanotechnology" have transformed the treatment of cancer. Advances in gene therapy, immunotherapy, and AI-driven diagnostics further refine patient-specific treatments. Minimally invasive surgical techniques and thermal ablation offer effective alternatives to tumor resection. The integration of AI, nanorobots, and engineered nanomaterials enhances early detection, targeted drug delivery, and treatment efficacy. Collaborative efforts in medicinal chemistry and AI will continue to drive breakthroughs in cancer therapeutics, improving patient outcomes.